Effect of Modified Lumbar Sustained Natural Apophyseal Glide on Low Back Pain in Postnatal Women - Soliman Eskands, Mina Nageb; Nashed, Azza Barmoud; Abdel-Halim Kaddah, Mohamed; Mahmoud Botla, Afaf Mohamed (Journal of Neonatal Surgery, 2025)
Background: Postnatal low back pain (LBP) is identified as pain that begins shortly after childbirth. It is located above the gluteal folds and below the costal borders. LBP negatively impacts women's quality of life. Sustained Natural Apophyseal Glide (SNAG) technique can improve spinal ROM and decrease pain. Purpose: To explore the efficacy of modified lumbar SNAG on postpartum LBP. Methods: Sixty participants between the ages of 20 and 35 who had been experiencing LBP postnatally for at least three months and whose BMI was < 30 kg/m² were chosen from the Kasr El Ainy University Hospitals' outpatient clinics. They were distributed into two equal-number groups at random; the control group (A) (n=30) performed only traditional exercises (strengthening and stretching exercises for back and abdominal muscles) for 30 min/session, trice weekly for four weeks. Study group (B) (n=30) received Modified “SNAGs” on the affected lumbar level (L4-L5) for 10 sec for 3 sets/session, trice weekly for four weeks, plus the same exercise program as group (A). The two groups’ participants were assessed before and after treatment utilizing the visual analogue scale (VAS) to determine pain severity and the Oswestry Disability Index (ODI) to assess functional disability. Results: The mean values of pain severity and functional disability in both groups decreased statistically significantly after treatment, with group (B) showing the greatest improvement. Conclusion: The use of modified SNAGs was beneficial in treating postpartum LBP, and its integration with traditional exercises was more beneficial than traditional exercises alone.